(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Fatmawati F, Sibero T, Trianto A, Wiyanti DP, Sabdono A, Pronggenies D, Radjasa OK. 2022. The influence of fermentation using marine yeast Hortaea werneckii SUCCY001 on antibacterial and antioxidant activity of Gracilaria verrucosa. Biodiversitas 23: 5258-5266. Gracilaria verrrucosa is producer of agar, a polysaccharide, that widely used in pharmaceutical and food industries. However, several studies have shown that the secondary metabolite of this seaweed is not potential as an antimicrobial and antioxidant agents. This study aimed to determine the antibacterial and antioxidant properties of methanolic extract of G. verrucosa after fermentation using marine yeast Hortaea werneckii SUCCY001. The samples were fermented based on different optimization times, specially in three, six and nine days. Samples were extracted using methanol by maceration method. Then the extracts were tested for antimicrobial potential against the several human clinical pathogens namely Bacillus cereus, Bacillus subtilis, Escherichia coli, Micrococcus luteus and Pseudomonas aeruginosa. The antioxidant potential was analyzed using the 1,1-diphenyl-2-picrylhydracyl (DPPH) and 2,2-Azinobis 3-ethyl benzothiazoline 6- sulfonic acid (ABTS) method while total phenolic content (TPC) was measured using Folin-Ciocalteu. Secondary metabolites were characterized using thin layer chromatography (TLC) and GC-MS. TLC plate visualization using UV light, DPPH, FeCl3 and vanillin-sulfuric acid reagents. The results showed that the extract fermented for nine days was able to inhibit the growth of P. aeruginosa and M. luteus at a concentration of 2 mg/mL. The highest antioxidant activity was found in the nine days fermented extract with an RSA value of 21.9% ± 0,0001 for DPPH and 12.53 % ± 0.002 for ABTS. Furthermore, the highest total phenolic content was found in the nine days fermented extract of 7.57 GAE/mg. The results of characterization using TLC showed the presence of phenolic compounds, terpenoids and antioxidants in fresh seaweed extracts, autoclaved fresh seaweed, three days of fermentation, six days and nine days. Based on this research, it can be seen that the addition of marine yeast starter H. werneckii SUCCY001 was able to increase the antibacterial and antioxidant activity of G. verrucosa.